Hypothesis: A new anteroposterior axis for non-radiate early echinoderms - de Lussanet, Marc HE (PeerJ Preprints, 2016)
Homalozoa are a weird group of echinoderms, for their complete lack of radiate symmetry. Indeed, they are typified by their tendency to marked asymmetric body forms. It has been proposed that they asymmetric forms evolved from bilaterally symmetric ones, but so far, only approximately bilaterally symmetric forms have been described (Robinson & Sprinkle 1969;Zamora 2012). Hypothesis: Homalozoans developed from bilaterally symmetric, tropartite larvae, by adopting a secondary anteroposterior axis.
Keywords: Echinoderm paleontology; asymmetry; evo-devo; homalozoan; stylophoran; homostelean; homoiostelea; theory